Biochemical role of the collagen-rich tumour microenvironment in pancreatic cancer progression - Shields, Mario A. (Biochem J, 2012)
PDAC (pancreatic ductal adenocarcinoma) is among the most deadly of human malignances. A hallmark of the disease is a pronounced collagen-rich fibrotic extracellular matrix known as the desmoplastic reaction. Intriguingly, it is precisely these areas of fibrosis in which human PDAC tumours demonstrate increased expression of a key collagenase, MT1-MMP [membrane-type 1 MMP (matrix metalloproteinase); also known as MMP-14]. Furthermore, a cytokine known to mediate fibrosis in vivo, TGF-β1 (transforming growth factor-β1), is up-regulated in human PDAC tumours and can promote MT1-MMP expression. In the present review, we examine the regulation of PDAC progression through the interplay between type I collagen (the most common extracellular matrix present in human PDAC tumours), MT1-MMP and TGF-β1. Specifically, we examine the way in which signalling events through these pathways mediates invasion, regulates microRNAs and contributes to chemoresistance.